KEDUDUKAN AHLI BAHASA DALAM PEMBUKTIAN PERKARA PENCEMARAN NAMA BAIK (STUDI PUTUSAN NOMOR: 47/PID.SUS/2019/PN. MGT) - Putra, Ridho Ferdiansyah; Kristiyadi, Kristiyadi (Sebelas Maret University, 2023)
This study aims to determine how the role of linguists and criminal lawexperts in proving defamation cases through twitter. In addition, it is also to know the judge's consideration in deciding the case of defamation through twitter. The method used in this research is normative or doctrinal research. Legal materials includeprimary legal materials and secondary legal materials, the legal materials are arranged systematically, studied, then compared and a conclusion is drawn in relation to the problem under study. The collection of legal materials in this research uses courtdecision study techniques. The legal material analysis technique used is a qualitative analysis technique that uses a deductive thinking pattern. The use of the deduction method stems from the submission of major premises (general statements), then minor premises (special statements) are submitted, from the two premises a conclusion is drawn. Based on the results of research and discussion, it is concluded that experts have a position as evidence based on Article 184 paragraph (1) letter b of the Criminal Procedure Code (KUHAP). The results showed that the consideration of the panel of Judges in deciding to impose punishment on the Defendant was in accordance with Article 45 paragraph (3) Jo. Article 27 paragraph (3) of Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law of the Republic of Indonesia Number 11 of 2008 concerning Electronic Information and Transactions.Keywords: Expert role; defamation;judge's consideration